DNASE1L3 Mutations in Hypocomplementemic Urticarial Vasculitis Syndrome. Issue 8 (26th July 2013) - Özçakar, Z. Birsin; Foster, Joseph; Diaz‐Horta, Oscar; Kasapcopur, Ozgur; Fan, Yao‐Shan; Yalçınkaya, Fatoş; Tekin, Mustafa
<x xml:space="preserve">Abstract</x> Objective Hypocomplementemic urticarial vasculitis syndrome (HUVS) is characterized by recurrent urticaria along with dermal vasculitis, arthritis, and glomerulonephritis. Systemic lupus erythematosus (SLE) develops in >50% of patients with HUVS, although the pathogenesis is unknown. The aim of this study was to identify the causative DNA mutations in 2 families with autosomal‐recessive HUVS, in order to reveal the pathogenesis and facilitate the laboratory diagnosis. Methods Autozygosity mapping was combined with whole‐exome sequencing. Results In a family with 3 affected children, we identified a homozygous frameshift mutation, c.289_290delAC, in DNASE1L3. We subsequently identified another homozygous DNASE1L3 mutation leading to exon skipping, c.320+4delAGTA, in an unrelated family. The detected mutations led to loss of function, via either nonsense‐mediated messenger RNA decay or abolished endonuclease activity, as demonstrated by a plasmid nicking assay. Conclusion These results show that HUVS is caused by mutations in DNASE1L3, encoding an endonuclease that previously has been associated with SLE.